Biochemical and in silico Characterization of Recombinant L-Lactate Dehydrogenase of Theileria annulata - Nural, Belma; Erdemir, Aysegul; Mutlu, Ozal; Yakarsonmez, Sinem; Danis, Ozkan; Topuzogullari, Murat; Turgut-Balik, Dilek (HUMANA PRESS INC, 2016)
Theileria annulata is a parasite that causes theileriosis in cattle. Reports about drug resistance made essential to develop new drug. LDH of Theileria schizonts is the vital enzyme for its anaerobic metabolism. TaLDH gene was first cloned into pGEM-T cloning vector with two introns in our previous study. Here we report cloning of TaLDH without introns into pLATE 31 vector in E. coli BL21(DE3). Protein was in an inactive form. Two mutations were fixed to express the active protein. Protein was purified by affinity chromatography and evaluated by SDS-PAGE and size exclusion chromatography. Optimum pH of enzyme was performed in pH 7.5, and enzyme was stabilized at 20-40 A degrees C. Enzyme kinetics of recombinant TaLDH were found to be in the direction of pyruvate to lactate K (m) 0.1324 and K (i) 4.295 mM, k (cat) , 44.55/s and k (cat) /K (m) , 3.3693 x 10(5)/M/s. 3D structure of TaLDH was predicted, and possible drug binding sites were determined by homology modelling.
Keywords: LDH; Theileria annulata; Thermostability; Substrate inhibition; Homology modelling; PLASMODIUM-FALCIPARUM; TOXOPLASMA-GONDII; SUBSTRATE-INHIBITION; KINETIC-PROPERTIES; BINDING DOMAINS; DESIGN; BUPARVAQUONE; PARASITES; GENE; ANTIMALARIALS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology